2016
DOI: 10.1161/circulationaha.116.022913
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Prolonged PR Interval and Outcomes of Cardiac Resynchronization Therapy

Abstract: BACKGROUND A prolonged PR interval is common among cardiac resynchronization therapy (CRT) candidates; however, the association between PR interval and outcomes is unclear, and the data are conflicting. METHODS We conducted inverse probability weighted analyses of 26 451 CRT-eligible (ejection fraction ≤35, QRS ≥120 ms) patients from the National Cardiovascular Data Registry ICD Registry to assess the association between a prolonged PR interval (≥230 ms), receipt of CRT with defibrillator (CRT-D) versus impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 30 publications
2
30
0
2
Order By: Relevance
“…Since we did see trends for better response rates with aCRT, it is likely that our inclusion of only patients with normal AV intervals resulted in group sizes too small to detect differences. Additionally, patients with normal AV conduction may have been healthier at baseline, as a previous large registry study demonstrated that patients with pre‐CRT PR intervals of ≥230 ms had a greater risk of HF hospitalization or death than those with short PR intervals . Thus patients with normal AV conduction in our study could be less likely to exhibit improvements.…”
Section: Discussionmentioning
confidence: 87%
“…Since we did see trends for better response rates with aCRT, it is likely that our inclusion of only patients with normal AV intervals resulted in group sizes too small to detect differences. Additionally, patients with normal AV conduction may have been healthier at baseline, as a previous large registry study demonstrated that patients with pre‐CRT PR intervals of ≥230 ms had a greater risk of HF hospitalization or death than those with short PR intervals . Thus patients with normal AV conduction in our study could be less likely to exhibit improvements.…”
Section: Discussionmentioning
confidence: 87%
“…27 Finally, prolonged atrioventricular conduction which occurs in 15%-50% of patients undergoing CRT may limit the use of adaptive atrioventricular delay programming. 30,31 The use of HBP has the advantage of allowing for optimization of the atrioventricular interval in patients with atrioventricular conduction disease. The improvements in acute electrical resynchronization were also seen in the subgroup of patients who underwent atrioventricular nodal ablation for AF in whom fusion of intrinsic activation with biventricular pacing would not be possible.…”
Section: Follow Upmentioning
confidence: 99%
“…[15][16][17][18] Subsequent analyses demonstrating patients with LBBB were more likely to benefit from CRT 3,19 (presumed due to greater extent of LV activation delay) 20 have underscored the importance of the electrical substrate. However, a significant minority of LBBB patients do not respond to CRT 19,21 and an important minority of non-LBBB patients do appear to benefit from CRT 22,23 although this remains controversial. Furthermore, it is increasingly recognized that optimal LV lead position [24][25][26] and device programming algorithms 27 affect CRT outcomes as they directly impact the activation wavefronts responsible for LV depolarization.…”
Section: Early Landmark Crt Trials Enrolled Patients With Qrs Prolongmentioning
confidence: 99%